Agent-Based Hierarchical Approach For Executing Bag-Of-Tasks In Clouds - Włodzimierz Funika; Kamil Mazurek; Wojciech Kruczkowski (Computer Science, 2014)
Numerous unrelated, independent (no inter-task communication) tasks called “bag-oftasks”(BoTs) compared with message passing applications can be highly parallelised andexecuted in any acceptable order. A common practice when executing bag-of-tasks applications(BoT) is to exploit the master-slave topology. Cloud environments offer some featuresthat facilitate executing BoT applications. One of the approaches to control cloud resourcesis to use agents that can flexibly act in a dynamic environment. Given these assumptions wedesigned a combination of these approaches, which can be classified as: a distributed, hierarchicalsolution to the issue of scalable executing of bag-of-tasks. The concept of our systemrelates to a project that is focused on processing huge quantities of data incoming from anetwork of sensors by the Internet. Our aim is to create a mechanism for processing such dataas a system which executes jobs while exploiting load balancing for cloud resources using,e.g., Eucalyptus. The idea is to create a hybrid architecture which takes advantage of somecentralized parts of the system and full distributedness in other parts. On the other handwe balance dependencies between the system components using a hierarchic master-slavestructure.